Encyclopedia of Analytical Chemistry 2010
DOI: 10.1002/9780470027318.a9034
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy of Catalysts

Abstract: This chapter focuses on the application of Raman spectroscopy for characterizing catalytic materials and for the investigation of the bulk and surface chemistry occurring during catalyst preparation and operation; a general theoretical background and description of equipment for Raman experimentation is also presented. Over the past decades, Raman spectroscopy has increasingly been applied for characterization of all types of catalytic materials: bulk and supported metals, bulk mixed metal oxides, supported me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 270 publications
0
6
0
Order By: Relevance
“…Raman spectroscopy is a great complement to XRD since, unlike XRD, it can also detect crystalline nanoparticles smaller <4 nm and amorphous phases that cannot be detected by XRD. 48 Raman spectroscopy was utilized to investigate the oxide phases present in the 5, 10, and 20% EISA powders, and the spectra are presented in Figure 4 with that of the bulk NiO reference. The main NiO band at 1101 cm −1 is present in all the samples indicating that the bulk NiO phase is retained upon Fe addition, in agreement with XRD data.…”
Section: Acs Catalysismentioning
confidence: 99%
“…Raman spectroscopy is a great complement to XRD since, unlike XRD, it can also detect crystalline nanoparticles smaller <4 nm and amorphous phases that cannot be detected by XRD. 48 Raman spectroscopy was utilized to investigate the oxide phases present in the 5, 10, and 20% EISA powders, and the spectra are presented in Figure 4 with that of the bulk NiO reference. The main NiO band at 1101 cm −1 is present in all the samples indicating that the bulk NiO phase is retained upon Fe addition, in agreement with XRD data.…”
Section: Acs Catalysismentioning
confidence: 99%
“…V, Mo, W, and Re) and many pertinent reviews are available. [12][13][14][15][16][17][18][19][20][21][22][23][24] Despite the extent of the literature, the reports on key aspects such as the termination configuration (i.e. discriminating between the mono-oxo, di-oxo and/or trioxo termination configurations) of dehydrated MO x sites and the eventual heterogeneity of the dispersed oxometallic phase (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…(WO x ) n phase, particularly when advanced synthesis routes based on molecular approaches are followed, thereby in some cases enabling catalyst design. 15,26,27 In addition, it has been reported, without sufficient evidence, that the prevalent configurations obtained after calcination by the deposited species do not revert/change with temperature under dehydrating conditions, [16][17][18][19][20][21][22][23][24][25] despite the sound evidence to the contrary documented in scarce reports. 28 Recently, however, we have provided strong evidence that controverts the soundness of the above statement and showed that a temperature-dependent transformation takes place under dehydrated conditions between the sites of distinct configurations in rhenia supported on TiO 2 and low-loaded tungsta and molybdena supported on TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…18 A qualitative change has become apparent in the last decade to further consolidate in situ spectroscopy of the working catalyst: to demonstrate that the spectra correspond to an operating catalyst, simultaneous quantitative analysis of the reaction progress (e.g., by gas chromatography) has to be performed, and in this case, the structure and activity can be correlated. The term ''operando,'' which is Latin for ''working,'' ''operating,'' was coined in 2000 by Ban˜ares [19][20][21][22][23] and proposed in the literature in 2002 to underline the simultaneous evaluation of both structure and catalytic performance, [23][24][25][26][27][28][29][30] including the use of a cell that delivers reaction kinetics data that match those obtained in an ideal reactor. Detailed analyses of kinetic aspects of the operando cell have been reported by Meunier.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Raman experiments can be carried out at virtually any temperature and pressure, without interference from the gas phase, with increasingly higher time-resolutions so that reaction kinetic data can be measured directly and correlated with the spectroscopic data. A number of monographs and review articles on Raman spectroscopy in heterogeneous catalysis have been published and have recently been reviewed, [27][28][29][30] very recently several exciting reviews address specific areas of progress for in situ Raman spectroscopy. [34][35][36] This work attempts to show how both in situ and operando Raman studies are a valuable tool to follow the transformations of the active metals for two different Ni-containing catalysts.…”
Section: Introductionmentioning
confidence: 99%